A study on the performance of composite slab using metal deck from maintenance aspect / Norhidayah Othman - Othman, Norhidayah (Faculty of Architecture, Planning and Surveying, 2009)
Composite construction in the modem times combines the high strength performance of structural steel with the stiffness and compressive strength inherent in concrete. Each of the two materials can be used to its best advantage and, therefore, composite structures have proved economical in terms of overall cost. They have become increasingly popular due to the economy and speed in construction. With the development of automated fabrication yards, the process of composite construction has been simplified enabling good quality control of products. Composite concrete slab on metal decking system are more better compare other floor system. This system has more advantages to make the fast track on the construction project. It is commonly employed in most of the buildings due to their efficient load carrying capacity and diaphragm action in the high-rise frames. This was necessary industrial development together with monitoring of works and maintenance. Hence, the building design must consider to the maintenance aspects. As such, maintenance works for composite floor also necessary to prolong the performances of the composite slab.